UBE2O remodels the proteome during terminal erythroid differentiation - Nguyen, Anthony; Dederer, Verena; Kawan, Mona; Kühnle, Nathalie (Science, 2017)
The degradation of excess subunits of protein complexes is a major quality-control problem for the cell. How such “orphans” are recognized and tagged for degradation is poorly understood. Two papers identify a protein quality-control pathway that acts on some of the most abundant protein complexes in the human body: hemoglobin and ribosomes (see the Perspective by Hampton and Dargemont). Yanagitani et al. show that the central player in this process is an unusual enzyme (UBE2O) that recognizes substrates and tags them for destruction. Other quality-contr ol pathways tend to use separate factors for target selection (often a chaperone), ubiquitin donation (an E2), and ubiquitin conjugati on (an E3). Encoding all three activities in a single factor whose function can be reconstituted in a purified system provides a tractable route to detailed mechanistic and structural dissection. Nguyen et al. show the importance of the UBE2O pathway in the differentiation of red blood cells.